Pengaruh Life Style, Brand Image, Dan Word Of Mouth Terhadap Keputusan Pembelian Smartphone Samsung (Studi Pada Mahasiswa S1 FEB Angkatan 2019) - Nur Fatimah; Muhammad Ridwan Basalamah; Ety Saraswati (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This study aims to determine the effect of lifestyle, brand image, and word of mouth on purchasing decisions for Samsung smartphones (a case study on FEB students class of 2019). This research used a descriptive quantitative method using primary data obtained by distributing questionnaires and measured using a Likert scale. The population in this study were FEB students class of 2019. The sample calculation in this study used the slovin formula which produced 90 respondents. The method of determining the sample is purposive sampling. The data analysis method used is instrument test: validity and reliability test, normality test, classic assumption test: multicollinearity test and heteroscedasticity test, multiple linear regression analysis, hypothesis testing: partial test and coefficient of determination. Partial research results show that life style has a significant effect on purchasing decisions, brand image has a significant effect on purchasing decisions, and word of mouth has a significant effect on purchasing decisions. Keywords: Life Syle, Brand Image, Word of Mouth, and Purchase Decision